2019
DOI: 10.4274/jus.galenos.2019.2688
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Urological Surgery Clinical Trials in the Middle East and Its Analysis in Comparison to Global

Abstract: To analyze the rates and types of ongoing urological surgery clinical trials (CTs) in the Middle East (ME) and worldwide. Materials and Methods: The number of urological surgery CTs was identified via the ClinicalTrials.gov database. Studies were further analyzed using different filters present in ClinicalTrials.gov. Results: Vast majority of urological surgery CTs are progressing in North America and Europe with 71.53%. The ME accounts for only 6.19%. In the ME, only Turkiye hosts studies of pediatric urologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…With regards to urologic diseases, there is a lack of knowledge regarding the specific disparity of the global distribution of ongoing clinical trials. A prior investigation found that the number of urologic clinical trials being conducted in the countries in the Middle East is lower than that as compared to studies being conducted in other countries (8). In this study, we compare the current distribution of ongoing clinical trials in LMICs with respect to urologic conditions.…”
Section: Introductionmentioning
confidence: 95%
“…With regards to urologic diseases, there is a lack of knowledge regarding the specific disparity of the global distribution of ongoing clinical trials. A prior investigation found that the number of urologic clinical trials being conducted in the countries in the Middle East is lower than that as compared to studies being conducted in other countries (8). In this study, we compare the current distribution of ongoing clinical trials in LMICs with respect to urologic conditions.…”
Section: Introductionmentioning
confidence: 95%